Nanoplateletsomes restrain metastatic tumor formation through decoy and active targeting in a preclinical mouse model - Longlong Zhang; Yuefei Zhu; Xunbin Wei; Xing Chen; Yang Li; Ying Zhu; Jiaxuan Xia; Yiheng Huang; Yongzhuo Huang; Jianxin Wang; Zhiqing Pang (Elsevier, 2022)
Platelets buoy up cancer metastasis via arresting cancer cells, enhancing their adhesion, and facilitating their extravasation through the vasculature. When deprived of intracellular and granular contents, platelet decoys could prevent metastatic tumor formation. Inspired by these, we developed nanoplatesomes by fusing platelet membranes with lipid membranes (P-Lipo) to restrain metastatic tumor formation more efficiently. It was shown nanoplateletsomes bound with circulating tumor cells (CTC) efficiently, interfered with CTC arrest by vessel endothelial cells, CTC extravasation through endothelial layers, and epithelial-mesenchymal transition of tumor cells as nanodecoys. More importantly, in the mouse breast tumor metastasis model, nanoplateletsomes could decrease CTC survival in the blood and counteract metastatic tumor growth efficiently by inhibiting the inflammation and suppressing CTC escape. Therefore, nanoplatelesomes might usher in a new avenue to suppress lung metastasis.